Kebijakan Ekonomi Di Masa Pandemi Covid-19 - Nur Afni (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2021)
COVID-19 discovered a global pandemic that gave rise to the emergence of various groups, especially the public. Inaugurated by the World Health Organization as a global pandemic, the management of COVID-19 is a challenge for countries with limited energy sources and health care systems. Citizens' understanding continues to grow along with the number of positive problems and deaths due to COVID-19 which continues to grow in a relatively short time. The ability of each country to adapt to the existing conditions during efficient and anticipatory implementation varies greatly. The policy finds an early ground that must be tested in order to be able to tackle these cases successfully. Anticipatory policy decisions related to efforts to prevent the spread of COVID-19, take action against infected patients, protect health workers, and control public awareness are carefully considered. For this reason, the Government is trying to schedule a New Normal policy so that the economic impact of the pandemic does not create a sustainable crisis. This policy is linked to planning where the Government has established programs, as well as major projects in the 2020-2024 National Medium-Term Development Plan (RPJMN). The government needs to review the medium-term plan considering that in 2020 all programs that are trying to focus on taking action against Covid-19. The government has 3 alternatives in the medium term, whether it is always quality, making moderate improvements, or changing it with a new plan with assumptions made from the Covid-19 pandemic and the consequences that accompany it.